2005
DOI: 10.1002/lsm.20185
|View full text |Cite
|
Sign up to set email alerts
|

Pc 4 photodynamic therapy of U87‐derived human glioma in the nude rat

Abstract: These results warrant expanding this pre-clinical study to seek effective baseline Pc 4 drug- and light-doses and infusion-to-photoirradiation timing that would be necessary for a Pc 4-mediated PDT clinical trial for glioma patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
25
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
4
3
2

Relationship

5
4

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 38 publications
(38 reference statements)
0
25
0
Order By: Relevance
“…Pc 4 has been found to be highly effective against numerous human cancer cells in vitro and model tumor systems (2025). PDT with Pc 4 is currently in clinical trials for psoriasis and CTCL (14, 26, 27), and other applications are being developed.…”
Section: Discussionmentioning
confidence: 99%
“…Pc 4 has been found to be highly effective against numerous human cancer cells in vitro and model tumor systems (2025). PDT with Pc 4 is currently in clinical trials for psoriasis and CTCL (14, 26, 27), and other applications are being developed.…”
Section: Discussionmentioning
confidence: 99%
“…To test this possible application for DCE-MRI, we are studying DCE-MRI taken before and after PDT using the phthalocyanine photosensitizer, Pc 4, of U87-derived intracerebral tumors in an athymic nude rat model [5]. We hypothesized that an increase in permeability of the U87-derived tumor space would occur following open surgical delivery of the light necessary for Pc 4-PDT.…”
Section: Introductionmentioning
confidence: 99%
“…These preclinical results suggest that Pc 4 merits further study as a potential photosensitizing agent in clinical trials on PDT of glioma. 5 A larger pre-clinical study is warranted to investigate appropriate light and drug doses and the interval between light and drug administration. However, additional research is necessary to determine a means of assessing the specificity and sensitivity of brain tumors in patients that would enroll in a prospective this clinical trial.…”
Section: Introductionmentioning
confidence: 99%
“…Our model has been the athymic nude rat following intracranial implantation of U87 cells (American Type Culture Collection [ATCC], Manassas, VA). 5 The U87 immortalized human glioma cell line gives rise to tumors roughly one week after parenchymal implantation of cells in the athymic nude rat brain. We have found that selective uptake of Pc 4 in these tumors was 3.8 times greater than in the surrounding normal brain tissue 5 and that following administration of Pc 4 these tumors are highly sensitive to PDT.…”
Section: Introductionmentioning
confidence: 99%